Long-term premorbid blood pressure and cerebral small vessel disease burden on imaging in transient ischemic attack and ischemic stroke - Lau, K; Li, L; Simoni, M; Mehta, Z; Küker, W; Rothwell, P; Oxford Vascular Study (American Heart Association, 2018)
Background and Purpose— Studies of causes of cerebral small vessel disease (SVD) should fully adjust for blood pressure (BP), but most etiological studies use a single BP measurement or history of hypertension, which might underestimate the role of hypertension. In patients with transient ischemic attack and ischemic stroke, we therefore compared the associations of baseline and long-term premorbid BP with measures of SVD on magnetic resonance imaging brain. Methods— We studied 1009 transient ischemic attack/ischemic stroke patients who had a brain magnetic resonance imaging, in the population-based OXVASC (Oxford Vascular Study), and related baseline and 20-year premorbid BP (median: 15 readings/patient) to the total SVD score on imaging. Results— SVD score was associated with increasing mean baseline systolic BP (SBP; odds ratio of top versus bottom BP quartile: 2.28; [95% CI, 1.62–3.21]; P<0.0001) and with prior hypertension (2.53; [95% CI, 2.01–3.20]; P<0.0001), but the association was much stronger with mean premorbid SBP (6.09; [95% CI, 4.34–8.55]; P<0.0001). Mean diastolic BP at baseline was negatively associated with SVD score (0.71; [95% CI, 0.51–1.00]; P=0.050), and a positive association was only evident for diastolic BP 10 to 20 years previously (3.35; [95% CI, 2.33–4.84]; both P<0.0001). Relationships between overall mean premorbid BP and SVD burden were strongest in patients age <70 (SBP: 6.99; 4.11–11.86; diastolic BP: 3.13; 1.95–5.07; both P<0.0001) versus ≥70 years (2.37; 1.42–3.94; P=0.001; and 1.16; 0.74–1.84; P=0.52). Conclusions— Mean premorbid SBP is more strongly associated with SVD burden than baseline SBP or history of hypertension, and baseline diastolic BP yields a misleading estimate of the likely etiological importance of midlife hypertension for the subsequent development of SVD. Studies of novel potential etiological factors for SVD should aim to adjust for long-term prior BP, and trials of BP lowering with only a few years of follow-up may underestimate the overall impact on SVD.